2020
DOI: 10.1136/bmjspcare-2019-001961
|View full text |Cite
|
Sign up to set email alerts
|

ePTFE/FEP stents for malignant biliary obstruction

Abstract: BackgroundBiliary obstruction due to malignant disease causes debilitating symptoms and palliation of the disease involves placement of biliary stents. Covered self-expanding metal biliary stents may provide a longer patency and a lower risk of complications and dysfunction compared to uncovered stents, making them better for patients’ quality of life and cost effectiveness. This study aims to evaluate the indications and outcomes for a group of cases where expanded polytetrafluoroethylene/fluorinated ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The median survival in patients with covered stents was 79 and 92 days with bare stents. Another study focused on covered stents only and describes the results of a 4‐year follow‐up period 49 . A very similar median patency of the stent was observed, with 173 days, but the median survival time much higher, with 247 days.…”
Section: Clinical Trial Of Eptfe Medical Devicesmentioning
confidence: 90%
“…The median survival in patients with covered stents was 79 and 92 days with bare stents. Another study focused on covered stents only and describes the results of a 4‐year follow‐up period 49 . A very similar median patency of the stent was observed, with 173 days, but the median survival time much higher, with 247 days.…”
Section: Clinical Trial Of Eptfe Medical Devicesmentioning
confidence: 90%
“…It is also important to select an appropriate stent placement location. Overlying stents should extend past the blocked area at both ends, otherwise there could be an increased risk of tumor overgrowth at the ends of the stent [ 4 ]. In addition, future development of novel tumor-specific biliary stents should broaden the scope of existing treatment strategies, and identify appropriate neoadjuvant therapies to improve long-term survival, develop stent patency, reduce stent migration, and reduce unnecessary re-interventions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The European Society of Gastrointestinal Endoscopy (ESGE) strongly recommends the use of self-expandable metal stents (SEMS) for palliative extrahepatic biliary obstruction (high quality evidence) [3]. Nonetheless, stent re-occlusion caused by tumor growth, overgrowth, connective tissue formation, and sludge formation, affects the application of this technology, increasing the probability of re-intervention and shortening the patency of a stent [4][5][6][7]. Studies have found that biliary stents combined with iodine-125 ( 125 I) seed strand implantation might effectively relieve obstructive jaundice and prolong stent patency [8][9][10].…”
Section: Purposementioning
confidence: 99%